Psychological features of the syndrome of emotional burnout of educators (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the problem of emotional burnout ofeducators. A theoretical overview of modern concepts of the phenomenon ispresented. An attempt is made to provide a detailed and definitive analysisof the basic concept. The basic essence of the phenomenon is determinedas a complex psychophysiological phenomenon that occurs as a result ofprolonged emotional overload, especially in the conditions of performing anactivity. The polyfactorial specificity and content-dynamic features of theemotional burnout syndrome of educational workers were revealed. Theneed to organize socio-psychological support for the teacher’s activities isemphasized, which provides for an improvement in working conditions andan increase in the energy-adaptive potential of educators
Keywords: emotional burnout, affective impotence, stress, overload, chronic fatigue, professional stress